Simulation in an SDN network scenario using the POX Controller - Prete, Ligia Rodrigues; Shinoda, Ailton Akira [UNESP]; Schweitzer, Christiane Marie [UNESP]; De Oliveira, Rogerio Leao Santos (Institute of Electrical and Electronics Engineers (IEEE), 2014)
Computer networks have evolved due to new trends in the society's needs since their emergence as a way of providing remote access and sharing of computational resources. The architecture inflexibility of the computer networks presents a challenge for researchers, since their experiments can hardly be evaluated in real networks. Thus, in general, tests of new technologies are conducted on network simulators, which imply in a streamline of the reality. The paradigm of Software Defined Networks (SDN) and OpenFlow architecture, offer a way for the implementation of a programmable network architecture, able to be implemented gradually in production networks, which offers the possibility of separating the control mechanisms of the many traffic flows served, so that a scientific experiment can be performed in a real network (adapted for SDN) without interfering with its operation. This paper contextualizes the existing problems in current computer networks, and presents the SDN network as one of the main proposals for the viability of the Internet of the Future. In this context, it is discussed the OpenFlow architecture, which allows the creation of applications for Software Defined Networks. Finally it is presented the network simulator SDN, the Mininet, which implements the OpenFlow interface in a network simulation scenario containing a controller POX with two components, one OpenFlow switch and three nodes. The main objective was to evaluate the communication and bandwidth between nodes. © 2014 IEEE.
Keywords: Future Internet; OpenFlow; POX; Software Defined Networks